1994
DOI: 10.1001/jama.1994.03520240043039
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Disease Progression According to Gender of Patients With HIV Infection

Abstract: Compared with men, HIV-infected women in the CPCRA were at increased risk of death but not disease progression. Risks of most incident opportunistic diseases were similar for women and men; however, women were at an increased risk of bacterial pneumonia. These findings may reflect differential access to health care and standard treatments or different socioeconomic status and social support for women compared with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…In one study, women were found to have an increased risk Thus, while there was a significantly lower serum virus load of death but not of disease progression [6]. This may be attriband a wider distribution of serum virus load values in women, uted to the fact that women may have more limited access to the rate of change in virus load over the study period was health care and poorer socioeconomic status than men in the similar in men and women.…”
Section: Resultsmentioning
confidence: 97%
“…In one study, women were found to have an increased risk Thus, while there was a significantly lower serum virus load of death but not of disease progression [6]. This may be attriband a wider distribution of serum virus load values in women, uted to the fact that women may have more limited access to the rate of change in virus load over the study period was health care and poorer socioeconomic status than men in the similar in men and women.…”
Section: Resultsmentioning
confidence: 97%
“…[5][6][7][8][9] The reasons for a shorter survival in this group are thus still unclear and have been attributed to inequalities in access to health care or to HIV treatment. 10 The Brazilian epidemic is a good scenario to investigate potential gender differences in AIDS prognosis. Nowhere else in the world was the increase in reported female AIDS cases faster and more remarkable.…”
Section: Introductionmentioning
confidence: 99%
“…This shift in the demographics of AIDS has been accompanied by a growing recognition that the clinical manifestation and outcomes of the disease in women and men may be different.3'4 A large prospective study conducted by Terry Beirn Community Programs for Clinical Research on AIDS recently found that HIV-infected women face an increased risk of death when compared with men; during a 15-month period of observation, women had a significantly lower rate of survival even though disease progression rates did not differ significantly by sex. 5 The authors of the study suggest that the reasons for excess mortality in HIVinfected women "might include lower socioeconomic status, homelessness, domestic violence, substance abuse, and the lack of social support." 5(P 1920) At present, there are few empirical data to support or refute their hypothesis.…”
Section: Introductionmentioning
confidence: 99%